2009
DOI: 10.1186/1471-2091-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the functional interaction between POSH and ALIX and the relevance to HIV-1 release

Abstract: Background: The ALG2-interacting protein X (ALIX)/AIP1 is an adaptor protein with multiple functions in intracellular protein trafficking that plays a central role in the biogenesis of enveloped viruses. The ubiquitin E3-ligase POSH (plenty of SH3) augments HIV-1 egress by facilitating the transport of Gag to the cell membrane. Recently, it was reported, that POSH interacts with ALIX and thereby enhances ALIX mediated phenotypes in Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…It has been recently reported that in overexpressing human cell lines, Alix interacts with and is ubiquitinated by the onechain ligases POSH and Nedd4-1 during the process of virus budding (25,26). It is noteworthy that the interaction of Alix with these two ligases was detected only in the presence of detergents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been recently reported that in overexpressing human cell lines, Alix interacts with and is ubiquitinated by the onechain ligases POSH and Nedd4-1 during the process of virus budding (25,26). It is noteworthy that the interaction of Alix with these two ligases was detected only in the presence of detergents.…”
Section: Discussionmentioning
confidence: 96%
“…It is noteworthy that among the proteins known to interact directly or indirectly with Alix are components of the ubiquitin pathway, including the deubiquitinating enzyme Doa4 and the E3 ubiquitin ligases Cbl, POSH (plenty of Src homology 3), and Nedd4-1 (25)(26)(27)(28). The latter two ligases have been shown to ubiquitinate and cooperate with Alix during the process of HIV-1 release.…”
mentioning
confidence: 99%
“…The expression plasmid containing hemagglutinin (HA)-tagged Ub (pHA-Ub) was obtained from H.-G. Kräusslich and is described elsewhere (28). Construction of pCMV-Flag-ALIX is described elsewhere (36).…”
Section: Plasmid Constructs and Small Interfering Rnamentioning
confidence: 99%
“…Indeed, several cellular factors involved in endosomal sorting pathways have been identified to play some roles in HIV-1 Gag trafficking and particle assembly. These factors include adaptor protein complexes (16 -18), GGA (Golgi-localized ␥-ear-containing, Arf binding) and Arf (ADP-ribosylation factor) proteins (19), annexin 2 (20), ubiquitin E3 ligase POSH (plenty of SH3s) (21,22), and SOCS1 (the suppressor of cytokine signaling 1) (23).…”
mentioning
confidence: 99%